ON THE ISSUE OF SEGMENTATION OF SPACE OBJECTS IMAGES AGAINST THE STARRY SKY BACKGROUND IN ASTRONOMICAL TELEVISION MEASURING SYSTEM FOR ARTIFICIAL SATELLITES OBSERVATION - Strygin, N. Z. (Одеські астрономічні публікації, 2009)
---